The Changing Poles: how Antarctic and Arctic science helps to inform and prepare the EU for changes in sea level rise and the global climate - Mottram, Ruth; Meijers, Andrew; Karcher, Michael; Wilkinson, Jeremy; Couser, Griffith; Elshout, Pjotr; Bearzotti, Chiara (Zenodo, 2024)
24 January 2024: Policy briefing. This policy briefing has been organised by the European Polar Board (EPB) with assistance from the European Parliament Intergroup European Bureau for Conservation and Development (EBCD) on behalf of the EU-funded projects OCEAN:ICE and Arctic PASSION.